Effects of Physical Exercise Interventions on Gait-Related Dual-Task Interference in Older Adults: A Systematic Review and Meta-Analysis - Prudence Plummer; Lisa A. Zukowski; Carol Giuliani; Amber M. Hall; David Zurakowski (2015)
Dual-task interference during walking can substantially limit mobility and increase the risk of falls among community-dwelling older adults. Previous systematic reviews examining intervention effects on dual-task gait and mobility have not assessed relative dual-task costs (DTC) or investigated whether there are differences in treatment-related changes based on the type of dual task or the type of control group. The purpose of this systematic review was to examine the effects of physical exercise interventions on dual-task performance during walking in older adults. A meta-analysis of randomized controlled trials (RCTs) compared treatment effects between physical exercise intervention and control groups on single- and dual-task gait speed and relative DTC on gait speed. A systematic search of the literature was conducted using the electronic databases PubMed, CINAHL, EMBASE, Web of Science, and PsycINFO searched up to September 19, 2014. Randomized, nonrandomized, and uncontrolled studies published in English and involving older adults were selected. Studies had to include a physical exercise intervention protocol and measure gait parameters during continuous, unobstructed walking in single- and dual-task conditions before and after the intervention. Of 614 abstracts, 21 studies met the inclusion criteria and were included in the systematic review. Fourteen RCTs were included in the meta-analysis. The mean difference between the intervention and control groups significantly favored the intervention for single-task gait speed (mean difference: 0.06 m/s, 95% CI: 0.03, 0.10, p < 0.001), dual-task gait speed (mean difference: 0.11 m/s, 95% CI 0.07, 0.15, p < 0.001), and DTC on gait speed (mean difference: 5.23%, 95% CI 1.40, 9.05, p = 0.007). Evidence from subgroup comparisons showed no difference in treatment-related changes between cognitive-motor and motor-motor dual tasks, or when interventions were compared to active or inactive controls. In summary, physical exercise interventions can improve dual-task walking in older adults primarily by increasing the speed at which individuals walk in dual-task conditions. Currently, evidence concerning whether physical exercise interventions reduce DTC or alter the self-selected dual-task strategy during unobstructed walking is greatly lacking, mainly due to the failure of studies to measure and report reciprocal dual-task effects on the non-gait task.